Manufacture of electrical transformer cores that operate at medium and high frequencies (Journal of the College of Basic Education, 2023)
Fratia samples of chains Nc(Fe+Ni+Zn+Cu), N(Fe+Ni+Zn) and Ncc(Fe+Ni+Zn+Cu+Co) with a compact structure, bulk density of 4.93 g/cm3, and particle size of 20µm were prepared. To obtain the transmittance up to 700 in the range 0.1-20 MHZ (). We obtained electrical and magnetic losses in the high frequency range, and in most cases it is less than 0.085 due to the high electrical resistivity, in addition to the large and homogeneous granular sizes of the prepared samples, and this reduced the eddy currents to a large extent, which facilitates use in the field of high frequencies without loss. The magnetic hysteresis of the models N6, Nc3, Ncc3 obtained from them low values of the force force Hc (20A/m) and the precession flux Br (60mT) with a high value of the saturation flux Bs (310mT). .